2011
DOI: 10.1007/s00044-011-9657-6
|View full text |Cite
|
Sign up to set email alerts
|

Formulation of cashew nut shell liquid (CSNL) nanoemulsion, a potent inhibitor of human MCF-7 breast cancer cell proliferation

Abstract: Cashew nut shell liquid (CSNL) nanoemulsion has been formulated and its cytotoxic activity was determined using human breast cancer cells (MCF-7) adopting MTT assay and established staining techniques. MCF-7 cells treated with CSNL nanoemulsion suffered loss of viability and death mostly through apoptosis and/or necrosis as evidenced by the changes in the nuclear morphology and cytoplasmic features. The IC 50 value of 48-h treatment groups fall in the range of 88 ± 14.2 ll/ml. In conclusion, the antiproliferat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
10
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
4
4
1

Relationship

0
9

Authors

Journals

citations
Cited by 18 publications
(11 citation statements)
references
References 16 publications
(17 reference statements)
0
10
0
Order By: Relevance
“…Several data proved that CNSL and its derivatives possess interesting in vitro and in vivo biological functions, including antioxidant, antimicrobial, anti-cancer and larvicidal activities. [16][17][18][19][20][21] CA is able to form a stable nanovesicle dispersion upon combination with cholesterol, 22,23 showing good antioxidant and cytotoxic properties, 24 and a potential stabilization capability towards the encapsulated molecules. 25 A new challenge nowadays is, hence, the possibility of creating a biocompatible drug delivery system starting from waste materials, which can also be potentially used as a bioimaging tool.…”
Section: Introductionmentioning
confidence: 99%
“…Several data proved that CNSL and its derivatives possess interesting in vitro and in vivo biological functions, including antioxidant, antimicrobial, anti-cancer and larvicidal activities. [16][17][18][19][20][21] CA is able to form a stable nanovesicle dispersion upon combination with cholesterol, 22,23 showing good antioxidant and cytotoxic properties, 24 and a potential stabilization capability towards the encapsulated molecules. 25 A new challenge nowadays is, hence, the possibility of creating a biocompatible drug delivery system starting from waste materials, which can also be potentially used as a bioimaging tool.…”
Section: Introductionmentioning
confidence: 99%
“…[11À14] Apart from current industrial uses, it has been demonstrated that the cashew nut deriving oils may exert antioxidant,[15À17] antifungal, [18] antibacterial [19] and larvicidal [20,21] activities. Moreover, recent studies showed the antitumour efficacy of CNSL-nanoemulsions towards breast cancer [22] as well as the biological activities of CA itself, as acetylcholinesterase inhibition against Alzheimer disease [23] and antiproliferative/cytotoxic activity [24] on cancer cell lines, were also studied.…”
Section: Introductionmentioning
confidence: 99%
“…Nanoemulsions prepared from cashew nut shell liquid showed cytotoxicity against human breast cancer cell line MCF-7. The cells treated with the nanoemulsion presented reduced viability, primarily through apoptosis or necrosis [46]. Cashew nut has also demonstrated a positive impact on cholesterol levels and systolic blood pressure.…”
Section: Bioavailability and Health-promoting Benefitsmentioning
confidence: 98%